Training for prevention of ACL injury: Incorporation of progressive landing skill challenges into a program - Herrington, L. C.; Comfort, P. (Strength and Conditioning Journal, 2013)
Anterior cruciate ligament (ACL) injuries are prevalent in sports, with a high chance of reinjury after surgery and a 50% chance of osteoarthritis in later life. Prevention of these injuries is essential; however, most programs, although effective initially, may have low adherence and transference to sport because of their long duration and closed skill (activities performed in a self-paced stable predictable training environment) approach. This article aims to provide an abbreviated and integrated acl injury prevention program that also incorporates open-skill random practice (not preplanned) activities, which should increase transference to the less predictable and more chaotic sporting environments. For a video abstract of this article, see video, supplemental digital content 1, http://links.lww.com/scj/a127